2019
DOI: 10.3390/met9060640
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of a Fiber Welded Socket-Joint Made of Powder Metallurgy Molybdenum Alloy

Abstract: Fiber welding of socket-joints made of nanostructured high-performance molybdenum alloy (NS Mo) was carried out to get a better understanding of the role of welding heat input. It was found that low heat input (i.e., high welding speed) resulted in significantly refined grains in the fusion zone (FZ) of fiber laser welded NS Mo joints. When welding heat input decreased from 3600 J/cm (i.e., 1.2 kW, 20 cm/min) to 250 J/cm (i.e., 2.5 kW, 600 cm/min), the tensile strength of welded joints increased from about 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Particularly, the high-pressure residual gases in the micropores are the most harmful. During the welding process, these high-pressure gases can expand rapidly in the molten pool after being released into the high-temperature molten pool, which seriously deteriorates the quality of welded joints of Mo and Mo alloys [11][12][13].…”
Section: Pore Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, the high-pressure residual gases in the micropores are the most harmful. During the welding process, these high-pressure gases can expand rapidly in the molten pool after being released into the high-temperature molten pool, which seriously deteriorates the quality of welded joints of Mo and Mo alloys [11][12][13].…”
Section: Pore Defectsmentioning
confidence: 99%
“…The combined structure of laser welding and brazing is shown in Figure 12, joints with the same strength as base material and hydraulic bursting pressure of 60 MPa were produced using a combination of the two methods. Xie et al (2019) [12] found that low heat input (i.e., high welding speed) resulted in significantly refined grains in the fusion zone (FZ) of fiber laser welded nano-sized rare earth oxide particles and superfine crystal microstructure (NS) Mo joints, the cross-sectional microstructures of the NS Mo alloy laser welding joints is shown in Figure 11. When welding heat input decreased from 3600 J/cm (i.e., 1.2 kW, 20 cm/min) to 250 J/cm (i.e., 2.5 kW, 600 cm/min), the tensile strength of welded joints increased from~250 MPa to~570 MPa.…”
Section: Laser Weldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Mo is used to prepare nuclear fuel claddings that can withstand serious accident conditions for a long time [6]. Replacing traditional nuclear fuel rod claddings with Mo claddings can improve the safety of nuclear power, which has been increasingly concerned with relevant researches in recent years [7][8][9]. Welding is a key step in preparing nuclear fuel cladding tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the upper end plugs with holes were welded and sealed using RFW without upset forging in a high-pressure helium atmosphere. Research on laser welding of Mo claddings can be found in research published elsewhere [8,9]. This study focused on the feasibility of using RFW without upset forging to seal the last weld spots on the upper end plugs of Mo fuel claddings, so as to provide guidance for developing reliable welding technology for fuel claddings made of Mo.…”
Section: Introductionmentioning
confidence: 99%